Developing Emotionally Literate Staff : a Practical Guide. - Morris, Elizabeth, 1953- (Sage Publications, 2005)
'My feeling is that this is what some struggling institutions need'-. Times Educational Supplement Extra for Special Needs. Emotionally literate schools show better learning outcomes for children, improved attendance, reduced behavioural challenges, good relationships, improved recruitment and retention and have a well-motivated, effective and less stressed workforce. In this practical book, Elizabeth Morris and Julie Casey provide everything you need to begin to create an emotionally literate ethos within your school, and give you tools to develop emotionally literate staff and practices in y.